Congo - Marshall, Frank; Kennedy, Kathleen; Mercer, Sam; Shanley, John Patrick; Walsh, Dylan; Linney, Laura; Hudson, Ernie; Heslov, Grant, 1963-; Baker, Joe Don; Curry, Tim; Goldsmith, Jerry; Crichton, Michael, 1942-2008; et al. ([Hollywood, Calif.] : Paramount, 1999)
An expedition to return a gorilla to Africa and find the Lost City of Zinj and its diamond mines encounters a variety of dangers.
Originally produced as motion picture in 1995.
Based on the novel by Michael Crichton.
Includes 2 theatrical trailers.
Music, Jerry Goldsmith ; editor, Anne V. Coates ; director of photography, Allen Daviau.
Dylan Walsh, Laura Linney, Ernie Hudson, Grant Heslov, Joe Don Baker, Tim Curry.
MPAA rating: PG-13, for jungle adventure terror and actin and brief strong language.
Keywords: Crichton, Michael, -- 1942-2008 -- Film and video adaptations; Gorilla -- Congo (Democratic Republic) -- Drama; Democratic Republic of the Congo -- Drama; Feature films; Adventure films; Films for the hearing impaired; French language materials -- Bilingual; Video (DVD)